Guinness world records 2014 - Glenday, Craig; Guinness World Records Limited ([London] Guinness World Records, 2013)
Lists records, superlatives, and unusual facts in the areas of fame, business, crime, the natural world, technology, war, the arts, music, fashion, and sports.
Introduction -- Dynamict Earth -- Animal Extremes -- Human body -- Pioneers -- Circus -- Extraordinary Exploits -- Society -- Urban Life -- Engineering -- Science & Technology -- At Your Leisure -- Sports.
"Augmented reality, see it 3D" --Cover.
Keywords: World records; Curiosities and wonders